2011
DOI: 10.1177/0009922811400730
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physician—Parent Discussions and a Brief Intervention on Caregivers’ Plan to Discipline: Is it Time for a New Approach?

Abstract: Consecutive English- or Spanish-speaking caregivers of 1- to 5-year-old children were randomized to view a multimedia program (approximately 5-10 minutes) in a pediatric primary care clinic. After the clinic visit, 258/259 caregivers participated in a brief personal interview. In the multivariate logistic model, caregivers were more likely to have been assisted in their plans to discipline if they had had a discussion about discipline with their physician (odds ratio [OR] = 4.93; 95% confidence interval [CI] =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…With a new approach in which parents had discussions and were asked to view the multimedia intervention, 89% of parents revised their plans to discipline their child. 12 The ethnically diverse population in this study is important because discipline strategies vary between cultures, 32 and both parents and physicians have reported cultural challenges related to discussions about discipline. 33,34 We found that parents of different sociodemographic backgrounds uniformly valued the intervention, albeit for somewhat different reasons.…”
Section: Resource For Othersmentioning
confidence: 99%
“…With a new approach in which parents had discussions and were asked to view the multimedia intervention, 89% of parents revised their plans to discipline their child. 12 The ethnically diverse population in this study is important because discipline strategies vary between cultures, 32 and both parents and physicians have reported cultural challenges related to discussions about discipline. 33,34 We found that parents of different sociodemographic backgrounds uniformly valued the intervention, albeit for somewhat different reasons.…”
Section: Resource For Othersmentioning
confidence: 99%
“…Parents gained knowledge of normal child development, insight into why children misbehave, and learned alternative behavior management strategies. [96][97][98][99] It is important to note that videos, including public service announcements on television, work best when the speaker is a peer (eg, an African American teenage mother speaking to other African American teenage mothers about the virtues of breastfeeding). 1 Mendelsohn et al 100 showed that replaying videotapes in which parents served as their own role models and when aided by live professional commentary is an effective way to increase positive parent-child interactions.…”
Section: Videosmentioning
confidence: 99%
“…The intervention required no additional physician time and automatically printed a summary report for the medical record. Parents who completed the intervention showed superior knowledge of child development, behavior, and safety issues than did Scholer et al 95,96,98,99 conducted numerous studies on "Play Nicely," an interactive DVD approach to managing children' s aggression. Parents viewing the program (within which they can select specific topics of interest) were significantly more likely than controls to report better management of children' s problematic behavior.…”
Section: 90mentioning
confidence: 99%
See 1 more Smart Citation
“…For clinicians, multimedia educational materials provide an effective 19 and resource-efficient tool for enhancing existing behavioral care. In accordance to previous findings, the results of this study strengthen the conclusion that a strong majority of parents, particularly those who have concerns about their child's behavior, will receive multimedia-based behavioral interventions positively.…”
Section: Discussionmentioning
confidence: 99%